Evolution of Staphylococcus aureus under Vancomycin Selective Pressure: the Role of the Small-Colony Variant Phenotype - Lenhard, Justin R. (Antimicrob Agents Chemother, 2015)
Staphylococcus aureus small-colony variants (SCVs) often persist despite antibiotic therapy. Against a 10(8)-CFU/ml methicillin-resistant S. aureus (MRSA) (strain COL) population of which 0%, 1%, 10%, 50%, or 100% was an isogenic hemB knockout (Ia48) subpopulation displaying the SCV phenotype, vancomycin achieved maximal reductions of 4.99, 5.39, 4.50, 3.28, and 1.66 log(10) CFU/ml over 48 h. Vancomycin at ≥16 mg/liter shifted a population from 50% SCV cells at 0 h to 100% SCV cells at 48 h, which was well characterized by a Hill-type model (R(2) > 0.90).